Perlindungan Hukum Kelompok Minoritas (Studi Analisa Peraturan Gubernur Jawa Timur Nomor 188/94/KPTS/013/2011 terhadap Kelompok Jamaah Ahmadiyah Indonesia di Jawa Timur) - Setiyawan, Imas; Isa, Abdullah (Taruna Law: Journal of Law and Syariah, 2023)
In Indonesia, the Ahmadiyah have been rejected since 1950 and have gained legitimacy since the MUI issued a fatwa in the 1980. Then at the MUI national working meeting in 1984, it wa stated that the qadian Ahmadiyah deviated from islamic teachings and disturbed state order. In addition,, the regional government of east java province has issued a decree of the governor of east java number 188/94/KPTS/013/2011, namely the prohibition of the activities of the indonesian Ahmadiyah community (JAI) in east java. Thid study aims to review the implications of the eas java governor’s decision number 188/94/KPTS/013/2011 cocerning the prohibition of the activities of the Ahmadiyah community in east java, and to find out the development of the Ahmadiyah community in east java province after receiving the east java governor’s decision 188/94/KPTS/013/2011 cocerning the prohibition of the activities of the Ahmadiyah community in east java. This study uses a qualitative approach. Reseacrhers used observation, interview, and documentation techniques to obtain data. Then use deductive reasoning in explaining conclusions. The result of this study stated that the implications of the decree of the governor of east java number 188/94/KPTS/013/2011 regarding the prohibition of the activities of the east java Ahmadiyah community against the Ahmadiyah community in east java, causing several impacts, namely impacts, social impacts, and legal impacts. Then the development of the Ahmadiyah community in east java after receiving the decision of the governor of east java number 188/94/KPTS/013/2011 is to continue to carry out activities as usual, for individual routines the Ahmadiyah community continues to do it like other muslims, but for comprehensive activities, the Ahmadiyah community is sometimes still hampered by permission from the security forces.